Trickster's queen ebook - Pierce, Tamora (Daughter of the Lioness, 2004)
The stage is set for revolution. Legends will rise in this dramatic  New York Times  and  USA Today  bestselling conclusion to  Trickster’s Choice,  the spy adventure from the fantasy author who is legend herself: Tamora Pierce! No longer a slave, Aly has risen through the ranks of the rebellion to become a master of spies. And just in time, she is brought out of exile and into the heart of the snakes’ den that is the Copper Isles royal court. Still, Aly must keep her wager with the trickster god and protect her charges: Sarai, the beautiful, dramatic, and rash potential queen, and Dove, the more cautious and often overlooked younger sister. Can they step out of the shadows and prove they’re a force to be reckoned with?   As the revolution builds, Aly’s relationship with half crow, half man Nawat deepens. But he must be prepared to step into a role bigger than his personal desires. And Aly must balance her passion for overthrowing the cruel leaders with the dangers lurking around every corner. Can she rise to the challenge . . . and what price must she pay for changing a kingdom’s destiny?   “Tamora Pierce’s books shaped me not only as a young writer but also as a young woman. She is a pillar, an icon, and an inspiration. Cracking open one of her marvelous novels always feels like coming home.” — SARAH J. MAAS , #1  New York Times  bestselling author   “Tamora Pierce didn’t just blaze a trail. Her heroines cut a swath through the fantasy world with wit, strength, and savvy. Her stories still lead the vanguard today. Pierce is the real lioness, and we’re all just running to keep pace.” — LEIGH BARDUGO , #1  New York Times  bestselling author